Association of ZFHX3 Genetic Polymorphisms and Extra-Pulmonary Vein Triggers in Patients With Atrial Fibrillation Who Underwent Catheter Ablation - Hwang, Inseok; Kwon, Oh-Seok; Hong, Myunghee; Yang, Song-Yi; Park, Je-Wook; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Physiology, 2022)
Abstract Background The ZFHX3 gene (16q22) is the second most highly associated gene with atrial fibrillation (AF) and is related to inflammation and fibrosis. We hypothesized that ZFHX3 is associated with extra-pulmonary vein (PV) triggers, left atrial (LA) structural remodeling, and poor rhythm outcomes of AF catheter ablation (AFCA). Methods We included 1782 patients who underwent a de novo AFCA (73.5% male, 59.410.8 years old, 65.9% paroxysmal AF) and genome-wide association study and divided them into discovery (n=891) and replication cohorts (n=891). All included patients underwent isoproterenol provocation tests and LA voltage mapping. We analyzed the ZFHX3, extra-PV trigger-related factors, and rhythm outcomes. Result Among 14 single-nucleotide polymorphisms (SNPs) of ZFHX3, rs13336412, rs61208973, rs2106259, rs12927436, and rs1858801 were associated with extra-PV triggers. In the overall patient group, extra-PV triggers were independently associated with the ZFHX3 polygenic risk score (PRS) (OR 1.65 [1.22-2.22], p=0.001, model 1) and a low LA voltage (OR 0.74 [0.56-0.97], p=0.029, model 2). During 49.940.3 months of follow-up, clinical recurrence of AF was significantly higher in patients with extra-PV triggers (Log-rank p<0.001, HR 1.89 [1.49-2.39], p<0.001, model 1), large LA dimensions (Log-rank p<0.001, HR 1.03 [1.01-1.05], p=0.002, model 2), and low LA voltages (Log-rank p<0.001, HR 0.73 [0.61-0.86], p<0.001, model 2) but not the ZFHX3 PRS (Log-rank p=0.819). Conclusions The extra-PV triggers had significant associations with both ZFHX3 genetic polymorphisms and acquired LA remodeling. Although extra-PV triggers were an independent predictor of AF recurrence after AFCA, the studied AF risk SNPs intronic in ZFHX3 were not associated with AF recurrence.